Thrombectomy for Acute Ischemic Stroke With a New Device-Skyflow: Study Protocol for a Prospective, Multicenter, Stratified Randomized, Single-Blinded, Parallel, Positive Controlled, Non-inferiority Clinical Trial - Liu, Huan; Li, Zhaoshuo; Zhu, Liangfu; Zhou, Tengfei; Wu, Qiaowei; He, Yanyan; Song, Xintong; He, Yingkun; Li, Tianxiao (Frontiers in Neurology, 2021)
Abstract Background: Stent retriever thrombectomy is the standard treatment for acute ischemic stroke with large vessel occlusion in anterior circulation. The aim of the trial is to evaluate whether the new thrombectomy device-Skyflow can achieve the same safety and efficacy as Solitaire FR in the treatment. Method: This study is a prospective, multicenter, stratified randomized, single blind, paralleled, positive controlled, non-inferiority clinical trial. The safety and efficacy of vascular recanalization in acute ischemic stroke patients who are treated with either a new thrombectomy device-Skyflow or with Solitaire FR and within 8 hours of symptom onset will be compared. A total of 192 patients will be enrolled, each group with 96 patients. The primary endpoint is successful recanalization rate after the operation. The secondary efficacy endpoints are the time from artery puncture to successful recanalization (TICI 2b-3), NIHSS scores 24h(18-36h) and 7±2days after the operation, mRS scores and the rate of patients with 0-2 scores 90±14 days after the operation, and the success rate of instrument operation. The safety endpoints are the rate of symptomatic intracranial hemorrhage(sICH) and subarachnoid hemorrhage at 24 h (18-36h) post-operation, incidence of adverse events (AE) and serious adverse events(SAE) , all-cause mortality and incidence of device defects. Discussion: This trial will provide information on the safety and efficacy of Sky-flow stent retriever in the treatment of acute ischemic stroke patients with anterior circulation large vessel occlusion. The success of this trial will be the basis for the product to be finally officially listed and applied in China.